Doctor’s Legal Obligation to Act as a Good Samaritan in Indonesia: Is It Ethically Justifiable? - Henryanto, Agathon; Oswari, Jessica Sylvanie (Mimbar Hukum, 2025)
Abstract The Good Samaritan Law, which principles are widely implemented globally, were not applied under Indonesia’s legal framework. Instead of ensuring adequate legal protection for “the Good Samaritan,” Indonesian law enforces their obligations under threat of legal repercussions. The law is even stricter when the Good Samaritan is a doctor. Current regulations create dilemmas for doctors especially when facing emergency situations, torn between saving lives and avoiding legal consequences. To address this, our paper employs normative (doctrinal) legal research which proposes three solutions: Firstly, Indonesian law should adopt the comprehensive Good Samaritan Law model. Second, shifting burdens of proof from doctors to the complainants. Lastly, it is crucial to synchronize the mechanism to submit a complaint against doctors to the authoritative institutions. These aim to overcome the legal and ethical issues surrounding the obligations and protections for doctors acting as Good Samaritans in Indonesia. Abstrak